Sistem Informasi Simpan Pinjam Pada Koperasi Sedia Kec.Tangen Menggunakan Php Mysql Dan Sms Gateway - Indrawati, Dian Gigih, Heru Supriyono, ST. MSc. PhD (2016)
Credit unions are financial institutions Salain bank is in charge of providing services to the community, in the form of money and a storage place for the community. Sedia Kec.Tangen Cooperative is one of the organizations of savings and loans as welfare unit members, especially teachers in Kec.Tangen environment. In cooperative "Sedia" Kec.Tangen transaction management savings, loans or installment still manually or bookkeeping and not well organized. Unavoidable recording manually prone to error, then Cooperative "Sedia" Kec.Tangen is a need for a system software update that replaces the work initially still manually into a computer system equipped SMS Gateway feature that will provide information on the number of deposits, the loan amount and monthly installments. The purpose of this study was to design and make a savings and loan information system that can terekap neatly inside the computer system, and can provide information about savings and loans to members malalui SMS Gateway. Systems based saving information WEB SMS gateway feature is designed using the PHP programming language and stored in a MySQL database. In the manufacture of Gammu SMS Gateway using the application. A WEB designed to treasurer of the cooperative as admin useful for processing data on cooperatives as well as an SMS Gateway feature to inform the total amount of savings, the total amount of the loan and the monthly installments are weighted to teachers or members of the cooperative are the results of this study. Based on the results of the questionnaire showed that 84% of the 20 respondents indicated that the system is made very helpful in computerized data storage.